2011
DOI: 10.1159/000328904
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Blood Products in Rotator Cuff Repair

Abstract: We review the management of rotator cuff tears, the mechanism of action of autologous blood products, principally platelet-rich plasma, and the current evidence for effective use of platelet-rich plasma, particularly in relation to the shoulder and chronic rotator cuff tears, for biological augmentation of rotator cuff repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This classification system is based on the absolute number of platelets (P), the method of platelet activation (A), and the presence/absence of white cells (W). Recently, PRP has been utilized for numerous musculoskeletal indications such as rotator cuff repair 3,4 , patellar tendinopathy 5 , knee osteoarthritis 6 , lateral epicondylitis 7 , osteochondral lesions of the talus 8 , and many other orthopaedic conditions. PRP induces musculoskeletal healing through a number of effects.…”
Section: Introductionmentioning
confidence: 99%
“…This classification system is based on the absolute number of platelets (P), the method of platelet activation (A), and the presence/absence of white cells (W). Recently, PRP has been utilized for numerous musculoskeletal indications such as rotator cuff repair 3,4 , patellar tendinopathy 5 , knee osteoarthritis 6 , lateral epicondylitis 7 , osteochondral lesions of the talus 8 , and many other orthopaedic conditions. PRP induces musculoskeletal healing through a number of effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lately PRP has become very popular among the orthopaedic community as a minimally invasive way of enhancing tissue healing in different conditions including rotator cuff repair [ 14 , 15 ], patellar tendinopathy [ 16 , 17 ], knee osteoarthritis [ 18 ], lateral epicondylitis [ 19 ], osteochondral lesions of the talus [ 20 ] and other orthopaedic conditions. It has been postulated that PRP promotes soft tissue healing by delivering a higher than normal concentration of platelets and therefore increased concentration of platelet derived growth factors to the diseased area [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 8 ] Several studies have reported the healing potential of autologous platelet-rich plasma (PRP) on tendons and especially on those of the rotator cuff. [ 9 10 11 12 13 ] They have been shown to decrease postoperative pain and to improve early clinical results. [ 14 ] These autologous conditioned plasma (ACP) are rich in growth factors, contained in the a-granules of the platelets.…”
Section: Introductionmentioning
confidence: 99%